Relevance of peripheral eosinophilia in chronic pancreatitis - Vutukuru, Venkatarami Reddy; V., Raghavendra Rao R.; Mathai, Varughese; Settipalli, Sarala (International Surgery Journal, 2019)
Background: Eosinophilia in peripheral blood has been observed in few patients with chronic pancreatitis (CP) but the clinical significance and the causes are not well understood. The aim was to analyse the features of CP in patients with and without eosinophilia and compare both groups and assess its significance. Methods: All patients diagnosed to have CP during period June 2009 to July 2012 were included in the study. Patients were divided into two groups based on eosinophil count in peripheral blood. Those with eosinophil count >0.6x109/L (6%) were considered as having eosinophilia. Author had analyzed and compared the clinical features of CP in patients with and without eosinophilia. Results: There were 28 (24.56%) patients with eosinophilia among 114 CP patients. Mean age at presentation was similar in two groups. The male to female ratio was significantly higher in patients with eosinophilia (p=0.03). Patients with eosinophilia had higher incidence of pancreas enlargement (78.57% vs. 37.2%, p=0.007). Mean intraductal pressures (20.42 vs. 22.52; p=0.05) and average pancreatic ductal diameter (7.85 vs. 8.90; p=0.03) were lower in patients with eosinophilia. The incidence of complications was significantly more in patients with eosinophilia (85.71% vs. 20.93%; p=<0.001). There was no infiltration of eosinophils in all the pancreatic tissue samples analysed in both groups. Conclusions: Association of eosinophilia with CP is a relatively common entity. It is associated with significantly increased incidence of disease related inflammatory complications, but the exact mechanism is not clear. Whether eosinophilia is a cause or effect of complication is not clear.